Recurrent desmoid tumor of the abdominal wall - Toughrai, Imane (The African Field Epidemiology Network, 2012)
Desmoid tumors most often occur in abdominal wall. Their tendency to recur lead to repeated operations which can make the abdominal wall reconstruction difficult. We report a 28-year-old female history. The patient was referred to our hospital for a recurrent desmoid tumor of the abdominal wall. The tumor was totally removed. The reconstruction was successful and the patient recovery was uneventful. Radical surgery still the mainstay of the desmoid tumors treatement. In abdominal wall location, the reconstruction can be a real challenge. Many procedures are discussed in literature. We used a double layer mesh covered by a fascial bepedicled flap. Taking into account their unpredictable behaviour and treatment complications, recurrent abdominal desmoid tumors can be managed simply and efficiently.